Estimates of foreign exchange risk premia: A pricing Kernel approach - Lorenzo Cappiello; Nikolaos Panigirtzoglou (Queen Mary University of London, Department of Economics, 2005)
The goal of this study is to measure market prices of risk and the associated foreign exchange risk premia extending the approach proposed by Balduzzi and Robotti (2001) to an international framework. Estimations of minimum variance stochastic discount factors permits the determination of market prices of risk, which, in turn, in an international framework, allow to compute foreign exchange risk premia. Market prices of risk are time-varying and surge during financial turmoil. This may be interpreted as an increase of the investors' coefficient of risk aversion during turbulent financial markets. Foreign exchange risk premia are also time-varying and they exhibit most variation from the early '70s onwards, when the Bretton Wood exchange rate system collapsed.
Keywords: G12; G15; F31; 330; Foreign exchange; Risk premia; Pricing kernel; Wechselkursrisiko; Zinsparit\~AƒÂt; Risikopr\~AƒÂmie; Capital Asset Pricing Model; Theorie